2012
DOI: 10.1152/ajprenal.00092.2012
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 in renal ischemic injury

Abstract: Factors that initiate cellular damage and trigger the inflammatory response cascade and renal injury are not completely understood after renal ischemia-reperfusion injury (IRI). High-mobility group box-1 protein (HMGB1) is a damage-associated molecular pattern molecule that binds to chromatin, but upon signaling undergoes nuclear-cytoplasmic translocation and release from cells. Immunohistochemical and Western blot analysis identified HMGB1 nuclear-cytoplasmic translocation and release from renal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 86 publications
(136 reference statements)
6
57
0
Order By: Relevance
“…TNFα, is a key cytokine shown to be upregulated early following IR injury and to promote recruitment of lymphocytes to the ischaemic injury 41 . Other cytokines that have been implicated in IR injury in small animal models include IL-2 42 , IL-6 43 , IL8 44 , IL-17 45 and IFNγ 43 and these were measured in this study. A previous observational study in humans undergoing liver transplantation 46 measured circulating serum cytokine levels at 24 hours post transplantation and found that the in the majority of patients, circulating levels were below the detectable level especially IFNγ (99%) and TNFα (77%).…”
Section: Discussionmentioning
confidence: 99%
“…TNFα, is a key cytokine shown to be upregulated early following IR injury and to promote recruitment of lymphocytes to the ischaemic injury 41 . Other cytokines that have been implicated in IR injury in small animal models include IL-2 42 , IL-6 43 , IL8 44 , IL-17 45 and IFNγ 43 and these were measured in this study. A previous observational study in humans undergoing liver transplantation 46 measured circulating serum cytokine levels at 24 hours post transplantation and found that the in the majority of patients, circulating levels were below the detectable level especially IFNγ (99%) and TNFα (77%).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the existing dichotomy of HMGB1 effects shows that its proinflammatory potency prevails over its proregenerative properties: inhibition of HMGB1 secretion by pretreatment with ethyl pyruvate ameliorates both the AKI and, in contrast to the inhibition of exocytosis of Weibel-Palade bodies, the long-term fibrotic changes seen in the postischemic kidneys. 1,2 Experimental findings and analysis of literature presented above should evoke the realization that AKI is a paradigm of a localized damage triggering systemic inflammatory disease (Figure 3). Whereas the local inflammatory process, when unperturbed, has a tendency to resolve itself, the systemic inflammatory response, when sufficiently intense and/ or prolonged, may not only exacerbate the local disease, but can also involve other organs (heart, lungs, and liver), accounting for the increased mortality even in cases of a mild AKI.…”
Section: Systemic Inflammation: Three Waves Of Danger Signalingmentioning
confidence: 95%
“…89,100,[142][143][144][145][146] In addition, lethality in sepsis relates to the release of HMGB1, histones, decorin, or biglycan. 42,78,100,144 This process seems to preferentially involve DAMP-mediated endothelial dysfunction via TLR2/TLR4, which increases vascular permeability, shock, and hypoperfusion.…”
Section: Tubular Necrosismentioning
confidence: 99%